PrimeSpecPCR: Python toolkit for species-specific DNA primer design and specificity testing - Adam Kuzdraliński (SoftwareX, 2025)
PrimeSpecPCR is an open-source Python toolkit that automates the workflow of species-specific primer design (comprising forward primer, reverse primer, and probe) and validation. The software implements a modular architecture comprising four main components: (1) automated retrieval of genetic sequences from NCBI databases based on taxonomy identifiers; (2) multiple sequence alignment using MAFFT to generate consensus sequences; (3) thermodynamically optimized primer and probe design via Primer3-py; and (4) multi-tiered specificity testing against the NCBI GenBank database. The toolkit features a user-friendly graphical interface and customizable parameters for quantitative PCR (qPCR) applications. PrimeSpecPCR accelerates primer development through parallel processing, automatic caching of intermediate results, and production of interactive HTML reports that visualize specificity profiles across taxonomic groups, while minimizing human errors and ensuring reproducibility of results. This toolkit reduces the time-intensive, labour-demanding processes conventionally required for designing species-specific molecular assays.